3 - Institutional Transformations and Implications for Access and Quality in Public and Private Universities in Kenya: A Comparative Study - Otiende, James E. (Journal of Higher Education in Africa, 2006)
This paper discusses the implications of the rapid expansion and transformations in African universities on access and quality. Using the example of Kenya, it looks at both the transformations that have occurred in the number of institutions of higher learning and also in the structural diversity of programmes and enrolment. With public universities facing economic challenges, public-financed higher education is increasingly perceived to be wasteful economically and restrictive in access, and consequently working against the realization of equity and compromising quality due to dependence on receding central government finances. The paper situates this shift in thinking with the emergence of neo-liberalism in Africa in the 1980s and 1990s. It argues that these shifts, together with the fiscal crisis of African countries have accelerated the growth of private universities in Africa. This situation poses serious challenges to the quality of knowledge production and to teaching in private and public universities alike. To address issues of access and quality, the paper emphasizes the need for multidisciplinarity, diversification of courses, improved institutional management, greater equity, and quality monitoring and evaluation. The paper argues for improved institutional accountability through institutionaliza- tion of external quality control, and for mainstreaming and facilitating research. There is also need for government to assist private universities in sourcing the re- quired capital for their further development.